Sentiment analysis of restaurant reviews in Malaysia - Muritala, Babajide AbuBakr (2017)
The food and beverage industry in Malaysia is steadily growing but at a very competitive pace. The industry was forecasted to be worth USD 21 billion by 2015, and it is imperative that restaurant owners have a good knowledge of their customers’ preferences in order to stay ahead of the competition. The purpose of this study is to examine the overall sentiments towards restaurants in Malaysia, to identify the most important topics or sentiment drivers towards restaurants and to derive useful insights and recommendations for restaurant owners from the customers’ online reviews. About 4,914 customer reviews from 582 restaurants across 20 towns and cities in Malaysia were scraped off TripAdvisor.com and text analytics was carried out using SAS Text Miner and SAS Visual Analytics. The results indicated that there were generally positive sentiments toward restaurants and the most important topics for reviewers were: Price, staff quality (friendly staff and service quality), food quality, Malaysian staple foods, menu variety (diverse food choices), atmosphere/ambience, location, waiting time, parking and the overall dining experience.